2018
DOI: 10.1108/jedt-05-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of mobile cranes and determination of outriggers loading

Abstract: Purpose The purpose of this paper is to develop mathematical tools that are reliable and easily implementable in computer codes, which address the determination of the outriggers reaction of mobile cranes and the monitoring of the actual stability margin available during lift operations. Design/methodology/approach An algorithm that determines the load transmitted to the ground by a mobile crane with four outriggers has been developed. Static theory of rigid body is adopted for the development of the algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…These discussions were usually held in collaboration with three other researchers actively involved in crane operations, which further enhance the authenticity of such decisions. In this process, articles containing search keywords in their abstracts but did not investigate CLP were removed, such as Tam and Fung (2011) and Romanello (2018). Some other articles focused on the structural stability of cranes, such as El Ouni et al (2021), were also omitted.…”
Section: Methodsmentioning
confidence: 99%
“…These discussions were usually held in collaboration with three other researchers actively involved in crane operations, which further enhance the authenticity of such decisions. In this process, articles containing search keywords in their abstracts but did not investigate CLP were removed, such as Tam and Fung (2011) and Romanello (2018). Some other articles focused on the structural stability of cranes, such as El Ouni et al (2021), were also omitted.…”
Section: Methodsmentioning
confidence: 99%
“…At present, leveling mechanisms can be divided from the number of legs into three-point supports, four-point supports, six-point supports and many other ways (Romanello, 2018; Tang et al , 2021; Tang and Chen, 2017), as shown in Figure 2.…”
Section: Design and Selection Of Key Partsmentioning
confidence: 99%
“…These robots are vulnerable to rollover or tip over, especially when they work on uneven or sloped terrains, or when they exert large forces or move heavy payloads. Outriggers have been used as stabilizers in mobile cranes, for example, Jeng et al (2010) and Romanello (2018), and mobile robotics applications, for example, Ohashi et al (2016), to level these systems and increase their safety.…”
Section: Introductionmentioning
confidence: 99%